Explaining the slow U.S. recovery: 2010–2017. Issue 4 (October 2018) - Fair, Ray
Abstract This paper argues that the slow U.S. recovery after the 2008–2009 recession was due to sluggish government spending. The analysis uses a structural macroeconometric model. Conditional on government policy, the errors in predicting output for the 2009.4–2017.4 period are within what one would expect historically. Productivity and labor force participation are endogenous variables in the model, and so their behaviors in this period are a consequence of the slow growth rather than a cause.